C=(4;9;16;...;2500)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt \(\dfrac{a}{b}=\dfrac{b}{c}=\dfrac{c}{d}=\dfrac{d}{e}=K\)
=> a = bK, b = cK, c = dK, d = eK
Do đó: \(\dfrac{2a^4+3b^4+4c^4+5d^4}{2b^4+3c^4+4d^4+5e^4}\)
= \(\dfrac{2b^4K^4+3c^4K^4+4d^4K^4+5e^4K^4}{2b^4+3c^4+4d^4+5d^4}\)
= \(\dfrac{K^4\left(2b^4+3c^4+4d^4+5d^4\right)}{2b^4+3c^4+4d^4+5d^4}\)
= K4 (1)
\(\dfrac{a}{e}=\dfrac{bK}{e}=\dfrac{cK^2}{e}=\dfrac{dK^3}{e}=\dfrac{eK^4}{e}=K^4\left(2\right)\)
(1)(2) => \(\dfrac{2a^4+3b^4+4c^4+5d^4}{2b^4+3c^4+4d^4+5e^4}\) = \(\dfrac{a}{e}\)
Lần sau bạn vào fx viết đề cho rõ nhé :))
\(Gt\Leftrightarrow a^2+b^2+ab=c^2+d^2+cd\)
Bình 2 vế đc:
\(a^4+b^4+2a^3b+2ab^3+3a^2b^2\)\(=c^4+d^4+2c^3d+2cd^3+3c^2d^2\)
\(\Leftrightarrow2\left(a^4+b^4+2a^3b+2ab^3+3a^2b^2\right)\)\(=2\left(c^4+d^4+2c^3d+2cd^3+3c^2d^2\right)\)
\(\Leftrightarrow a^4+b^4+\left(a+b\right)^4=c^4+d^4+\left(c+d\right)^4\)